2009
DOI: 10.1152/ajpheart.00963.2008
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution wavelet analysis of time-dependent physiological responses in syncopal youths

Abstract: Our prior studies indicated that postural fainting relates to thoracic hypovolemia. A supranormal increase in initial vascular resistance was sustained by increased peripheral resistance until late during head-up tilt (HUT), whereas splanchnic resistance, cardiac output, and blood pressure (BP) decreased throughout HUT. Our aim in the present study was to investigate the alterations of baroreflex activity that occur in synchrony with the beat-to-beat time-dependent changes in heart rate (HR), BP, and total per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 36 publications
7
36
1
Order By: Relevance
“…The intervals selected corresponded on the average to the intervals measured in fainting subjects. Previously, we showed that this time period was sufficient for comparison with fainters and does not invoke a false-positive fainting response (24,25,41). Additionally, most of our fainters faint during a 10-min tilt, and the duration of the time intervals is similar between groups (see RESULTS).…”
Section: Description Of Methodssupporting
confidence: 63%
See 4 more Smart Citations
“…The intervals selected corresponded on the average to the intervals measured in fainting subjects. Previously, we showed that this time period was sufficient for comparison with fainters and does not invoke a false-positive fainting response (24,25,41). Additionally, most of our fainters faint during a 10-min tilt, and the duration of the time intervals is similar between groups (see RESULTS).…”
Section: Description Of Methodssupporting
confidence: 63%
“…Both are driven and entrained by the same strong oscillator. We have previously shown that high frequency (HF) HR variability power, characteristic of respiratory arrhythmia (variations in HR that occurs during breathing cycles), is increased for both AP and RR interval at the time of faint (24). Additionally, we (24) and Bernardi's group (31) have previously demonstrated that respiratory power increases at the time of faint.…”
Section: Comparison With the Literaturementioning
confidence: 91%
See 3 more Smart Citations